Asymmetrical Exchange Rates Effect on Indonesia's Trade Balance in Tourism - Maulana, Akbar; Dawood, Taufiq Carnegie; Zulham, Teuku (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
The main objective of this research is to analyze the effect of depreciation and real exchange rate appreciation on Indonesia's tourism trade balance bilaterally against Australia, China, Japan, Malaysia, and Singapore. Such analysis on bilateral relations have never been studied for developing markets countries, namely Indonesia. This study uses a linear ARDL approach and a nonlinear ARDL approach with the dependent variable on the tourism trade balance and the real exchange rate as independent variables. Income, foreign direct investment (FDI), and natural disasters as control variables. The empirical results show that Chinese and Japanese tourists respond positively to the depreciation in the real currency rate of exchange, thereby increasing Indonesia's tourism trade balance. Nonlinear ARDL shows that the relation concerning the real rate of exchange plus the balance of trade is non-symmetrical with respect to China and Japan, while Australia, Malaysia, and Singapore are symmetrical. These results suggest that the government should formulate policies to increase tourist visits from China and Japan. Further empirical results also found a J-curve pattern in Indonesia-China and Indonesia-Japan.